Neutral stress, emphatic stress, and sentence intonation in Advanced Standard Copenhagen Danish - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1980)
The relationship between stress and fundamental frequency in short declarative and syntactically unmarked interrogative sentences, both with emphasis for contrast in various positions, is investigated and compared to prosodically neutral statements and questions on the basis of recordings by four speakers. Emphasis for contrast has a radical influence on the course of fundamental frequency, to the extent that the stress group which contains the stressed syllable of the emphasized word and its neighbours tonally reduce to one stress group. The influence from emphasis seems to reach farther on marked (non-declarative) than on unmarked (declarative) contours. Durational differences between utterances with and without emphasis for contrast are small, consisting mainly in a slight lengthening of the emphasized stress group, a lengthening which is to some extent counterbalanced by a shortening of the preceding stress group, if any.